Digital Erasmus – a pan-European approach to teaching building performance and resilient design - Hopfe, Christina J.; Brembilla , Eleonora; McElroy, Lori B.; McLeod, Robert S.; Gustin, Matej; Costola, Daniel (CLIMA 2022 conference, 2022)
The global COVID-19 pandemic in 2020 has forced universities to completely re-think their teaching concepts to provide safe, remote teaching of students off-campus. One of the challenges of this rapid transition is ensuring that the quality of the learning experience remains high and that students are able to engage and thrive in this new and predominantly digital environment. This project, entitled ‘Digital Erasmus - a roadmap to using building performance simulation to achieve resilient design’, responds to this context by seeking to transform the learning experience of students in built environment disciplines using a continuous digital learning cycle. This paper outlines the concept of the program and the learning objectives that it responds to, as well as some initial results highlighting the programs opportunity for students to work collaboratively and transnationally. The program is still in its infancy but it is hoped that it can serve as a template for similar future online courses that will promote safe, interdisciplinary and engaging collaboration amongst students from different universities.